2013
DOI: 10.1021/ja405135f
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Efficiency of Autonomous Nano- and Microscale Motors

Abstract: We analyze the power conversion efficiency of different classes of autonomous nano- and micromotors. For bimetallic catalytic motors that operate by a self-electrophoretic mechanism, there are four stages of energy loss, and together they result in a power conversion efficiency on the order of 10(-9). The results of finite element modeling agree well with experimental measurements of the efficiency of catalytic Pt-Au nanorod motors. Modifications of the composition and shape of bimetallic catalytic motors were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
259
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 232 publications
(282 citation statements)
references
References 65 publications
(127 reference statements)
19
259
0
4
Order By: Relevance
“…In order to do so, we used the so-called swimmer efficiency [34,36,37], which is the swimmer's hydrodyamic power output over the total enthalpy produced by the reaction. We find that the most efficient way to self-propel is to have the surface reactions take place in an isolated spot on the surface of the pole in self-diffusiophoresis.…”
Section: Discussion and Outlookmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to do so, we used the so-called swimmer efficiency [34,36,37], which is the swimmer's hydrodyamic power output over the total enthalpy produced by the reaction. We find that the most efficient way to self-propel is to have the surface reactions take place in an isolated spot on the surface of the pole in self-diffusiophoresis.…”
Section: Discussion and Outlookmentioning
confidence: 99%
“…The concept of the efficiency of swimming has since been investigated by Sabass and Seifert, who showed that nanoparticles are far more efficient at self-propulsion than micron sized colloids [35] and examined this quantity the context of self-electrophoresis [36]. More recently, Wang et al [37] performed an analysis of the efficiency of various types of swimmers.…”
Section: Introductionmentioning
confidence: 99%
“…The ion distribution and electrical charges around the Au-Pt nanomotors operating by self-electrophoresis were simulated by using a finite element model. The simulation was carried out with the COMSOL multiphysics package (47). Details of this simulation model can be found in SI Text.…”
Section: Methodsmentioning
confidence: 99%
“…The electric field distribution around the motors was simulated by using the COMSOL multiphysics package (see ref. 47 for modeling details). Then, an electrophoretic velocity profile as a function of the distance between the tracer particle and the motor was calculated based on the electric field distribution (Fig.…”
Section: Significancementioning
confidence: 99%
“…Leveraging the high precision in the alignment, the linear dependence of speed on the inverse of size of nanomotors (1/l) down to submicrometers, is experimentally determined, confirming previous theoretical predictions. 14 Finally, the manipulation of catalytic nanomotors by E-fields is demonstrated for two applications: the dynamic loading, transport, and unloading of micro-targets to pre-patterned microdocks; and assembling and integration of a catalytic nanomotor on a rotary NEMS to power its continuous operation. …”
Section: Introductionmentioning
confidence: 99%